Vulnerability and Vulnerance: Marginalization of Women in 1 Timothy 2:12-15 - Panuntun, Daniel Fajar; Oddeng, Zulkifli (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Did 1 Timothy 2:12-15 serve to marginalize women? From a feminist and vulnerability standpoint, we suggest reinterpreting the text with using Leo G. Perdue Biblical Theology concept. In terms of vulnerance, Paul restricts the role of women for the sake of the salvation of the Christian community in Ephesus under the shepherding of Timothy. From a perspective of vulnerability, women's restriction can be attributed to the issue of inequality, the hierarchical structure of control and subjugation by the wealthy during that era, and the susceptibility of women to be misled by heretical beliefs at the time. The passage 1 Timothy 2:12-15 provides insight into the cultural marginalization of women during that era. Therefore, the present-day Christian community must actively advocate for gender equality by addressing the underlying factors that contribute to the marginalization of women.